Lupus Nephritis, the therapy and the role of Rituximab in resistant cases - Hussein A. Nasir (مجلة كلية الطب, 2014)
Background Systemic lupus erythematosus (SLE) is a common autoimmune disease that affects mainly young females and nephritis is an important complication of the disease that may end with end stage renal disease (ESRD). Early diagnosis and proper treatment is important in decreasing the morbidity. Multiple immunesupressor agents used and according to the histopathology stage of the disease, still the proper drug used and the duration and dose required not settled. Rituximab which is monoclonal antibody that reacts against CD20 antigen on lymphocytes that cause B cells depletion is recently introduced in treatment of lupus nephritis .